Pengembangan Sistem Informasi Manajemen Desa (E-Desa) Di Desa Pemali Kabupaten Bangka - Alim Bahri; Karmawan Karmawan (Indonesian Journal of Dedication and Educations, 2022)
Community service that has been carried out is the Making of aVillage Management Information System Application. Thisservice activity was carried out at a special request from thePemali Village Head. Pemali Village, Bangka Regency, everyyear there are village activities that involve researchers ordevotees from various fields of science. The existence of BangkaBelitung University academics is expected to contribute to thedevelopment and development of the village community and itssurroundings. Pemali Village has its own characteristics in termsof communication and information to its citizens. From thebeginning the village had an information system that developedwith a bulletin board mechanism and oral communication.However, because the data continues to grow in size, otherfacilities are needed to manage it so that it is more conceptualand systematic. The Village Information System actually grew inresponse to environmental developments, has now become anembryo capable of providing acceleration on public informationdisclosure, transparency and accountability in good governance.in storing data, calling data and processing data about the village.This aspect of effectiveness and efficiency is the emphasis on thebackground of the development of the village information systemby producing an output in the form of a Village ManagementInformation System Application (e-Desa) in Pemali Village,Bangka Regency. The results in the field are that theDevelopment of a Village Management Information System (EDesa) in Pemali Village, Bangka Regency is expected tofacilitate, accelerate and expedite the service of Pemali Villageapparatus to the community.